KONTROL SOSIAL TERHADAP PKL (PEDAGANG KAKI LIMA) DI KOMPLEKS PASAR BERSEHATI CALACA KECAMATAN WENANG KOTA MANADO - Rambing, Reymond Krestian; Tasik, Femmy C. M.; Mumu, Rudy (Universitas Sam Ratulangi, 2019)
The social welfare issues today are increasingly varied therefore need to be balanced with an intensive and coordinated countermeasure effort so that the purpose of development in the field of social welfare can succeed. One of the problems of social welfare today that requires countermeasures and solutions is the issue of street vendors.Street vendor activity allergy selling at local highways in front of the market environment located on the roadside is a type of street vendor that uses the physical means of carts that sell seasonal merchandise other than street vendor which uses carts, there are some traders use Pick Up cars who do their activities at the location, in addition there are some Street Vendor who do trade in the market at the location of the market entrance adjacent to the motor parking area, at Essentially the type of street vendor that performs such action is the street vendor which violates the rules of the parties who have the authority to control, but the motive for the street vendor to carry out such deviations activities is due to obtain the consumer And sales can be quick to sell, other than that competition with other street vendor is also quite large. So that traders try to make their trades first encountered by the consumer, especially for street vendor that sells seasonal merchandise.Â Keywords: street vendor, social welfare, market